Family language policy in post-genocide Matabeleland: The case of a Ndebele family. Issue 1 (2nd January 2022) - Maseko, Busani
Abstract: This study focuses on the perspectives of parents in a Ndebele heritage language family in post-Gukurahundi Matabeleland in Zimbabwe. Gukurahundi is a codename for a military operation that resulted in the killing of over 20 000 mainly Ndebele speakers in Matabeleland and the Midlands (of Zimbabwe) between 1983 and 1987. The failure by the state to publicly acknowledge and own the genocide has resulted in survivors deploying nuanced strategies in dealing with Gukurahundi inflicted trauma. This article examines how the focal parents' Gukurahundi language experiences are infused into their explicitly articulated family language policy. The study deploys Tannenbaum's reconceptualisation of family language policy as a coping and defence mechanism to demonstrate how the parents' emotional dispositions and orientations towards the use of their Ndebele heritage language as a form of coping strategy are enmeshed with memories of language prejudices experienced during Gukurahundi. The study also exposes how focal parents' reification of a Ndebelecentred family language policy is emotionally laden, and borders on the proscription of Shona as a defence against the reproduction of post-Gukurahundi state-wide Ndebele marginalisation in the family.